Smoking marihuana as a rare cause of pneumomediastinum – case report - Makarewicz, Wojciech; Łaski, Dariusz; Basiński, Andrzej; Śledziński, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Pneumomediastinum is defined as pathological presence of air in the mediastinum. Isolated, spontaneous pneumomediastinum is a benign condition, but its presence should always alert the clinician to look for its cause. We present a case of a young male, without any comorbidities, who presented pneumomediastinum linked to drug usage (smoking marihuana).